Design of Hypercontent Module of IPAS (MIPAS) on Magnetism, Electricity and Technology for 5th Grade Elementary School Student - Raihani, Sofi Safiqa; Yektyastuti, Resti; Effane, Anne; Rodriguez, Paula Andrea (Educational Researcher Journal, 2024)
Learning media in general is a tool in the learning process. With the rapid development of the times, learning media has also evolved from conventional learning media to digital learning media. Conventional learning often experiences obstacles such as difficulties in understanding. This design stems from these problems and the lack of availability of learning media/resources in schools. This media design aims to produce learning media, namely hypercontent module teaching materials for science and science subjects with magnetic material. Electricity and technology class V elementary school. In this design, the development model used in media development is the alessi and trolllip model which consists of 3 stages, namely planning, design and development. This digital-based media allows students to get richer learning output than conventional learning media. Students can view photos, learning videos, animations and simulations which can be done online. This Hypercontent Science Module teaching material can help students in the learning process in Class V Elementary School Science subjects, increase students' learning experience and make it easier for teachers during the learning process